Effect of molecular mass on adsorption of epoxy oligomerson water-toluene solution and dispersed filler interfaces - I. D. Simonov-Emeljanov; A. N. Trofimov; V. S. Kopytin; V. M. Komarov; G. A. Simakova (Тонкие химические технологии, 2012)
The effect of molecular mass on adsorption of epoxy oligomers on water-toluene solution interfaces and a glass dispersed filler surface was investigated. Comparison of results (experimental and calculated on the basis of the theoretical adsorption model of) indicated that adsorption on the water-toluene interface was monomolecular. On the contrary, adsorption on the glass dispersed filler surface was polymolecular.